Economic evaluation of fixed-dose drug combinations: A systematic review - Toi Lam Phung, Due The Ong, Nhi T. N. Ngo, Trang Thuy Pham, Ha Thi Nguyen, Khanh N.C. Duong,, Mai Thi Ngoc Dang, Matthew James Alcusky, Daniel J. Amante, Hoa L. Nguyen (Journal of Applied Pharmaceutical Science, 2024)
This study aimed to review the quality of published evidence on the cost-effectiveness of fixed-dose drug combinations (FDCs), summarize key methodologic assumptions, and make recommendations for future economic evaluations of FDCs. The search was conducted on four databases, namely Medline, Embase, Web of Science, and the International Network of Agencies for Health Technology Assessment. Studies were selected if they assessed the cost-effectiveness of FDCs compared to one or more single active ingredient dosage forms or placebo. The Consolidated Health Economic Evaluation Reporting Standards 2022 checklist was utilized for evaluating the quality of studies. The study protocol was registered in PROSPERO (CRD42021295388). A total of 39 studies were eligible for inclusion in the review. While most of the studies (n = 29) reported that FDCs are cost-effective, the comparator in the economic evaluations was not justified explicitly in most studies (n = 34). Modelling that examined cost-effectiveness did not incorporate medication adherence (n = 22), failing to consider a key advantage of FDCs. The majority of studies investigating FDCs reported that they were cost-effective interventions. However, further economic evaluations based on long-term clinical trials with larger populations are necessary. Also, future economic studies should incorporate superior treatment adherence with FDC into the model structure.
Keywords: Economic evaluation, fixed-dose combinations, methodology, polypill, systematic review